The Relationship between Transformational Leadership of Immediate Superiors, Organizational Culture, and Affective Commitment in Fitness Club Employees - Kyongmin Lee; Woojeong Cho (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
In an uncertain global business environment, eff ective human resource management is a crucial element in improving organizational eff ectiveness. However, relatively little research has examined the characteristics of transformational leadership and the types of organizational culture suitable for improving organizational eff ectiveness in the sport management fi eld. Thus, the purpose of this study was to examine the relationship between transformational leadership of immediate superiors, organizational culture, and aff ective commitment in fi tness club employees. For this purpose, a survey was given to a convenience sample of 300 employees of fi tness clubs working in the Gwangju and Dae-gu metropolitan cities in South Korea. The data were then analyzed using descriptive statistics, correlations, and multiple regression analysis. The major fi ndings of this study were as follows. First, transformational leadership had a signifi cant eff ect on the organizational culture in fi tness clubs. Second, transformational leadership had a signifi cant eff ect on aff ective commitment of employees of the fi tness clubs. Third, organizational culture had a signifi cant eff ect on aff ective commitment of employees in fi tness clubs. The fi ndings of this study may be helpful for fi tness clubs to determine the characteristics of transformational leadership and the types of organizational culture needed to improve aff ective commitment of employees.